IMTC 2001. Proceedings of the 18th IEEE Instrumentation and Measurement Technology Conference. Rediscovering Measurement in The
DOI: 10.1109/imtc.2001.929543
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wavelet transform and neural network for condition monitoring of rotodynamic machinery

Abstract: -This paper describes a novel method of rotodynamic machine condition monitoring using a wavelet transform and a neural network. A continuous wavelet transform is applied to the signals coUected from accelerometer. The transformed images are then extracted as unique characteristic features relating to the various types of machine conditions. In the experiment, four types of machine operating conditions have been investigated: a balanced shaft, an unbalanced shaft, a misaligned shaft and a defective bearing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Dynamic optimization is based on the change in running status of the hoist and repeated optimization, it's the fundamental points which is different from the traditional predictive control optimal control. In addition, predictive control adopts multiple steps optimization [4] , compared with the traditional way of one step optimization, it can obtain more dynamic parameters that can reflect the running state trend of the hoist , thus it can accurately overcome the effects of various interference so that predictive control can get good results in the application of vibration risk predictive control of the hoist [6] .…”
Section: The Predictive Control Principle Based On Vibration Signal Amentioning
confidence: 99%
“…Dynamic optimization is based on the change in running status of the hoist and repeated optimization, it's the fundamental points which is different from the traditional predictive control optimal control. In addition, predictive control adopts multiple steps optimization [4] , compared with the traditional way of one step optimization, it can obtain more dynamic parameters that can reflect the running state trend of the hoist , thus it can accurately overcome the effects of various interference so that predictive control can get good results in the application of vibration risk predictive control of the hoist [6] .…”
Section: The Predictive Control Principle Based On Vibration Signal Amentioning
confidence: 99%
“…Comparative studies of various vibration and AE signal acquisition methods were reported in [3][4][5]. Previous studies [6][7][8] confirmed that AE monitoring is more reliable than vibration monitoring, as the former can detect the subsurface crack growth, whereas the latter can at best detect a defect only when it emerges on the surface of a structure. Yashioka [9] described an AE system for source location.…”
Section: Introductionmentioning
confidence: 98%
“…The vibration signal reaches the vibration sensor through the complex transmission path of the mechanical system, and the fault signal is inevitably disturbed in the transmission process. The uncertain fault diagnosis information after transmission through the complex path is very easy to cause false diagnosis [2]. The occurrence of false diagnosis will lead to excessive maintenance or false maintenance, and even lead to major safety accidents [3].…”
Section: Introductionmentioning
confidence: 99%